Diversity of Macroalgae Species on Pramuka Island, Thousand Islands Regency, DKI Jakarta Province - Sri Handayani; Hilwa Syifa Fadhilah; Ulfa Ainisyifa (Journal of Tropical Biodiversity, 2023)
Macroalgae are marine plants that are included in the Thallophyta division because they cannot be distinguished between their roots, stems and leaves. Life is widespread in almost all coastal areas of Indonesia, including the coast of the Thousand Islands. Pramuka Island is included in the Thousand Islands Regency, DKI Jakarta Province. As an inhabited island, anthropogenic activities on Pramuka Island vary greatly, so that the waters on Pramuka Island cannot be separated from anthropogenic pressures that can threaten marine biota on Pramuka Island, one of which is macroalgae. The relationship between decreasing macroalgae diversity and environmental quality needs to be considered, because the presence and loss of macroalgae is very important for the sustainability of macroalgae in the Thousand Islands and their conservation. The aims of this study were (1) to determine the diversity of macroalgae on Pramuka Island; (2) to determine the relationship between diversity and water quality on Pramuka Island. The research method is a survey method using the quadratic transect method. Analysis of macroalgae species diversity data using the Shanon-Wiener diversity index. Dominance with the Simpson dominance index. The Diversity Index and Dominance Index were calculated using the PAST.4.0 software. The link between environmental quality and diversity uses Principal Component Analysis (PCA). The results showed that the diversity of macroalgae on Pramuka Island was in the medium category, which ranged from 1.273 to 2.281. The diversity of macroalgae in Pramuka Island waters is influenced by physical factors such as salinity, depth and current speed, temperature, brightness, TDS , and chemical factors of nitrate, DO, Hg;Pb;Cu;